The vitamin D receptor is essential for the replication of pseudorabies virus - Lei Zeng; Shu-Yi Wang; Meng-Hua Du; Bei-Bei Chu; Sheng-Li Ming (mBio)
ABSTRACT The vitamin D receptor (VDR) is a nuclear steroid receptor that regulates the expression of genes across various biological functions. However, the role of VDR in pseudorabies virus (PRV) infection has not yet been explored. We discovered that VDR positively influenced PRV proliferation because knockdown of VDR impaired PRV proliferation, whereas its overexpression promoted it. Additionally, we observed that PRV infection upregulated VDR transcription alongside 1,25-dihydroxyvitamin D3 (VD3) synthesis, contingent on p53 activation. Furthermore, VDR knockdown hindered PRV-induced lipid synthesis, implicating VDR’s involvement in this process. To decipher the mechanism behind VDR’s stimulation of lipid synthesis during PRV infection, we conducted RNA sequencing (RNA-seq) and found significant enrichment of genes in the Ca2+ signaling pathway. Measurements of Ca2+ indicated that VDR facilitated Ca2+ absorption. Moreover, the PI3K/AKT/mTORC1 and AMPK/mTORC1 pathways were also enriched in our RNA-seq data. Interfering with VDR expression, or chelating Ca2+ using BAPTA-AM, markedly impacted the activation of PI3K/AKT/mTORC1 and AMPK/mTORC1 pathways, lipid synthesis, and PRV proliferation. In summary, our study demonstrates that PRV infection promotes VDR expression, thereby enhancing Ca2+ absorption and activating PI3K/AKT/mTORC1- and AMPK/mTORC1-mediated lipid synthesis. Our findings offer new insights into strategies for PRV prevention.IMPORTANCEVitamin D, beyond its well-known benefits for bone health and immune function, also plays a pivotal role in regulating gene expression through its receptor, the vitamin D receptor (VDR). Although VDR’s influence spans multiple biological processes, its relationship with viral infections, particularly pseudorabies virus (PRV), remains underexplored. Our research illustrates a complex interplay where PRV infection boosts VDR expression, which in turn enhances Ca2+ absorption, leading to the activation of critical lipid synthesis pathways, PI3K/AKT/mTORC1 and AMPK/mTORC1. These findings not only deepen our understanding of the intricate dynamics between host molecular mechanisms and viral proliferation but also open avenues for exploring new strategies aimed at preventing PRV infection. By targeting components of the VDR-related signaling pathways, we can potentially develop novel therapeutic interventions against PRV and possibly other similar viral infections.